PERAN MEDIA PEMBELAJARAN DALAM UPAYA MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V SD IT BUNAYYA - Winarti; Dinie Anggraeni Dewi; Risda Fitria Anjanie (Pusat Riset dan Inovasi Nasional, 2023)
Abstract. The purpose of this study was to determine the role of instructional media in increasing the learning motivation of fifth grade students at SD IT Bunayya. This study used descriptive qualitative method. Data collection techniques in the form of observation and interviews. Sources of data obtained from class V teachers and students as research subjects. From the results of this study it can be concluded that the role of the learning environment has a very large influence on student learning motivation and the teacher's role in increasing student motivation, namely through an individual approach, special guidance and pleasure of learning so that students have good learning motivation.